Trauma, Survival, and Narrative Structure: A Study of Post Attempt Recovery in Salman Rushdie’s Knife: Meditations After an Attempted Murder - Nadeem, Zakra; Ali Hussnain (RADINKA JAYA UTAMA PUBLISHER, 2025)
This paper investigates how Salman Rushdie’s Knife: Meditations After an Attempted Murder employs a fragmented, non‑linear narrative to represent the multifaceted experience of trauma, survival, and post‑traumatic recovery. Drawing on trauma theory (Caruth, 1996; Herman, 1992) and narrative theory (Bakhtin, 1981; White, 1980), it argues that Rushdie’s meditative structure both mirrors the disorientation of post‑traumatic consciousness and serves as a mechanism of narrative repair. The analysis begins by situating Knife within the broader contexts of autobiographical and trauma‑narrative traditions, then outlines the theoretical underpinnings that foreground trauma’s resistance to linear narration and the potential for post‑traumatic growth. Subsequent sections examine how Rushdie’s strategic use of fragmentation, repetition, and shifts between public and private discourse enacts the ruptured temporality of trauma, and how his reflections on bodily wounds, existential questioning, and creative resilience underscore survival as an ongoing negotiation. Finally, the study explores writing itself as a therapeutic practice, showing how repetitive narrativization allows Rushdie to reclaim agency and reconfigure his identity. The paper concludes that Knife transcends conventional memoir, demonstrating how narrative form can both bear witness to psychic fracture and facilitate healing, ultimately modeling the potential for growth and creative renewal in the aftermath of violence.